2020
DOI: 10.1200/jco.2020.38.4_suppl.617
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of somatostatin analog (SSA) monotherapy for well-differentiated grade 3 (G3) gastroenteropancreatic neuroendocrine tumors (NETs).

Abstract: 617 Background: Currently, there is no published data on the efficacy of SSAs for well-differentiated G3 NETs. Randomized trials have demonstrated a progression-free survival (PFS) benefit and limited tumor response for lower grade 1-2 NETs, but the optimal systemic therapy for metastatic/unresectable G3 NETs is unknown. We sought to evaluate the efficacy of SSAs in G3 NETs. Methods: We performed a retrospective analysis of Mayo Clinic patients treated with SSAs for metastatic/unresectable G3 NETs, querying d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Other treatment regimens have been used in NET G3, including sunitinib, immune checkpoint inhibitors, and SSAs [10,31,32]. In a separate Mayo Clinic study, treatment response and survival were assessed in patients with NET G3 who received SSA (n = 14), finding ORR of 14.3%, DCR of 64.3%, and mPFS of 4.4 months (95% CI, 2.9-24) [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other treatment regimens have been used in NET G3, including sunitinib, immune checkpoint inhibitors, and SSAs [10,31,32]. In a separate Mayo Clinic study, treatment response and survival were assessed in patients with NET G3 who received SSA (n = 14), finding ORR of 14.3%, DCR of 64.3%, and mPFS of 4.4 months (95% CI, 2.9-24) [10].…”
Section: Discussionmentioning
confidence: 99%
“…In this retrospective analysis, we aim to evaluate the clinical outcomes of patients with NET G3 treated with different cytotoxic regimens at Mayo Clinic. SSA use in NET G3 is discussed in a separate retrospective Mayo Clinic study [10]. [11].…”
Section: Introductionmentioning
confidence: 99%
“…Limited data point to PRRT efficacy even in G3 NEN with high SSTR expression ( Lithgow et al 2021 ), which is consistent with the early plateau we observed in the relationship between Ki-67 and PFS. On the other hand, pivotal SSA studies included only patients with Ki-67 <10%, and small series indicate minimal effect in patients with G3 tumours ( McGarrah et al 2020 , Lithgow et al 2021 , Merola et al 2021 ). Interestingly, the European Society of Medical Oncology guidelines propose the use of everolimus before PRRT in G2 patients with Ki-67 >10% ( Pavel et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“… 25 Data regarding the use of SSAs in G3 NETs is scarce and SSAs were historically not recommended for high-grade NENs. McGarrah et al 26 reported a median PFS of 4.4 months and a disease control rate of 50% in 14 patients with G3 NETs receiving single-agent SSAs in any line of therapy. They concluded SSAs may present an attractive option given their favorable side-effect profile, a conclusion that is supported by our results.…”
Section: Discussionmentioning
confidence: 99%